Chapter 15 Not a camp but a garrison: martial life 'at home' - Hedenstierna-Jonson, Charlotte (Taylor & Francis, 2023)
While knowledge of Viking Age military structures such as ditches, camps and enclosures outside of Scandinavia is growing, possible counterparts in the Scandinavian regions are generally less known. But despite the lack of trenches, camps and enclosures, other traces of army life and organization are preserved. In this chapter, it is suggested that the so-called garrison in the Viking-era city of Birka, Sweden, constitutes an interesting counterpart to the camps. Despite the differences between them, not least in terms of temporality and relation to the surrounding region, a more detailed comparison of the archaeological source material also shows important similarities. The structural and material remains of the garrison are here put into context and questions are raised concerning differences in opportunities and needs for a martial organisation operating at home compared to the challenges facing an army acting away from home.